Analysis of Financial Performance In Company PT. Indofood Sukses Makmur Tbk. Based On Ratio Analysis Liquidity and Profitability Period 2015-2019. - Yasinta Asiani; Setyo Riyanto (Syntax Corporation Indonesia, 2020)
The industry is one sector that has an important role in the development of a country. One of them is an industry in Indonesia, and its products that are in great demand are consumer goods with specifications of food products and household goods. An assessment of a company's financial level can be done by analyzing the company's financial statements. The financial statements used are the balance sheet and income statement from 2015 to 2019. To find out whether the company's financial condition is in good condition, various analyzes can be performed. One analysis that can be used to determine the company's financial situation is financial ratio analysis. The purpose of this study is to assess the company's performance by using the financial ratio analysis of PT Indofood Sukses Makmur, Tbk on the Indonesia Stock Exchange. This research was conducted by conducting documentation techniques with data obtained from the financial statements of PT Indofood Sukses Makmur. Then analyzed using financial statement analysis consisting of liquidity ratios and profitability ratios. The analytical method used is a descriptive analysis using the measurement of liquidity ratios and profitability. Based on the calculation of ratio analysis from PT Indofood Sukses Makmur, the liquidity ratio has increased every year so that the company's condition can be categorized quite well. Whereas, based on profitability ratios, it shows an increasing number from year to year so that it can be said the state of the company is in a good position.